Exploring Pragmatic Functions and Linguistic Features Analysis for Some Terms of Endearment in Egyptian Colloquial Arabic as Discourse Markers - Abdeltawab, Samar (AUC Knowledge Fountain, 2025)
In Arabic and many languages, terms of endearment are used as discourse markers to express affection. However, their meanings differ depending on the pragmatic context in which they are said. Despite the abundance of research on terms of endearment in various languages, there is a noticeable lack of studies examining the pragmatic functions and linguistic features of these terms in Arabic. This research aims to fill this gap by providing a comprehensive exploration of the pragmatic functions and investigating the syntactic and morphological characteristics of selected terms of endearment in Egyptian colloquial Arabic. It offers a detailed analysis of their linguistic features, aiming to understand how they function and evolve within different linguistic contexts. The selected terms, such as /ḥabibi/, /ḍanayah/, /ˁinayyah/, /ruḥi/, and /naḍari/, are examined as discourse markers in Egyptian Arabic discourse. This study employs a combination of qualitative and quantitative approaches to analyze the data, with a greater emphasis on qualitative analysis. The qualitative approach allows for an in-depth exploration of the various pragmatic functions and the complexities of the linguistic features under investigation, capturing the contextual and interpretive aspects that quantitative methods may overlook. Meanwhile, the quantitative analysis, with its statistically significant insights, supports the findings by providing measurable insights into the percentage of these terms used, ensuring a comprehensive understanding of the research topic and thereby, reinforcing the study's rigor. The study investigates data from 14 Egyptian films and TV series representing the time period from the early 1900s to 2024. The analysis, guided by speech act and pragmatic theories, reveals that these terms serve multiple pragmatic functions beyond expressing affection, including reducing tension, showing power, and maintaining solidarity. The study's findings showed morphological and syntactic features of terms such as /ḥabibi/, /ḍanayah/, /ˁinayyah/, /ruḥi/, and /naḍari/, revealing both their structural formation and their syntactic flexibility. Morphologically, these terms are constructed through affixation, compounding, or reduplication processes, providing insights into their formation and variation. Syntactically, these terms demonstrate adaptability, functioning effectively as vocatives or noun phrases across different clause positions at the beginning, middle, or end without altering their inherent structure. The findings also revealed that the use of terms of endearment in Egyptian colloquial Arabic might be influenced by various social variables, such as the speaker's social status, gender, and the relationship between the interlocutors. These variables significantly impact the terms' choice, frequency, and function, with different social contexts eliciting their pragmatic use and meaning variations. The findings provide new insights into the complexity and versatility of terms of endearment in Egyptian Arabic.